A colorimetric and near -infrared ratiometric fluorescent probe for the determination of endogenous tyrosinase activity based on cyanine aggregation. Issue 18 (6th August 2019) - Zhang, Peng; Li, Shasha; Fu, Caixia; Zhang, Qian; Xiao, Yuzhe; Ding, Caifeng
Abstract : A ratiometric fluorescent probe for TYR activity with high sensitivity was developed based on the H-aggregation of a cyanine dye. Abstract : Melanoma is an aggressive malignant tumor that undergoes rapid growth and metastasis in a short time; tyrosinase (TYR) is an important biomarker for melanoma diagnosis as it is over-expressed in melanoma cells. Therefore, the detection of TYR activity is of great significance. Although several fluorescent probes have been reported for the determination of tyrosinase activity in vitro and in vivo, only few of them possess a ratiometric pattern to provide built-in self-calibration for signal correction. Herein, a novel cyanine-based fluorescent probe (Cy-tyr) for the ratiometric fluorescent detection of TYR activity was developed by virtue of the aggregation protocol as a new advancement in this field of melanoma detection. When TYR was applied to the probe Cy-tyr, the phenolic hydroxyl group was oxidized to achieve o -benzoquinone in the presence of oxygen, and the resulting cyanine products exhibited a strong tendency to undergo H-aggregation. Accordingly, the maximum absorption of this probe shifted from 630 nm to 516 nm, and a red fluorescence appeared at 560 nm accompanied by the diminishing of the near infrared (NIR) emission at 760 nm. The proposed ratiometric fluorescent probe showed a good signal-to-noise ratio, leading to high sensitivity for TYR activity with the LOD of 0.02 U mL −1 . Moreover, the probe was successfully applied to image endogenous TYR activity in the B16 cells and showed a complete lack of noise in other cells with lower TYR expressions.